Gage R&R Repeatability and Reproducibility Analysis on Wafer Chocolatos Length Measurement - Muhammad Naufaldi Rasyid; Hikmal Abrar; Budi Aribowo (Universitas Al Azhar Indonesia, 2025)
This study aims to evaluate the reliability of a measurement system using the Gage Repeatability and Reproducibility (Gage R&R) method on Chocolatos wafer length measurements. The experiment involved three appraisers, each measuring five wafers with three repeated trials. The collected data were processed through several steps to determine repeatability (EV), reproducibility (AV), and overall measurement system capability (%R&R). The results showed that the %R&R value was 95%, indicating that the gage system is not satisfactory. Furthermore, the repeatability value was higher than the reproducibility value, which suggests that the main source of measurement variation comes from the measuring instrument. Therefore, the gage requires maintenance and possibly redesign. This research highlights the importance of proper calibration and system evaluation to ensure measurement accuracy and reliability.